Crossfire - Smith, Wilbur A.; Churchill, David, 1959- (Smith, Wilbur A. Courtney series., 2025)
In 1943, British spy Saffron Courtney sails to New York on a mission to rally support for the war effort while secretly hunting a Nazi spy ring within the British Embassy in the latest addition to the series following Cloudburst.